2019
DOI: 10.7498/aps.68.20190179
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure neutron diffraction techniques based on Paris-Edingburgh press

Abstract: Since the 1990s, with the benefit of available large-volumed samples, wide detector windows, and portability, Paris-Edinburgh press has been widely used in neutron facilities to study the structures and physical properties of condensed matter under high-pressure extreme conditions. In the present study, We perform high-pressure neutron diffraction experiments in neutron source of China using the Paris-Edinburgh press. The experiments are carried out on a high-pressure neutron diffraction spectrometer (Fenghuan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Compared with Figure 2a–c and Figure 1a–c, it can be seen that the CdS nanoparticles in the thin films were melted together, which was in accordance with the previous report. [ 14 ] The R q of CdS thin films on the FTO increased to 16.5 nm of 0.72 m , 17.5 nm of 0.59 m , and 18.9 nm of 0.46 m , also increasing with the decrease of ammonia concentration (the corresponding AFM images are shown in Figure S3, Supporting Information). The energy‐dispersive spectrometer (EDS) analysis revealed that the atomic ratio of Cl:Cd in the CdS thin films was 0.10:1 of 0.72 m , 0.12:1 of 0.59 m , and 0.15:1 of 0.46 m from Figure S4, Supporting Information (the X‐ray diffraction [XRD] and UV–vis–NIR of the CdS thin films are also provided in Figure S5 and S6, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with Figure 2a–c and Figure 1a–c, it can be seen that the CdS nanoparticles in the thin films were melted together, which was in accordance with the previous report. [ 14 ] The R q of CdS thin films on the FTO increased to 16.5 nm of 0.72 m , 17.5 nm of 0.59 m , and 18.9 nm of 0.46 m , also increasing with the decrease of ammonia concentration (the corresponding AFM images are shown in Figure S3, Supporting Information). The energy‐dispersive spectrometer (EDS) analysis revealed that the atomic ratio of Cl:Cd in the CdS thin films was 0.10:1 of 0.72 m , 0.12:1 of 0.59 m , and 0.15:1 of 0.46 m from Figure S4, Supporting Information (the X‐ray diffraction [XRD] and UV–vis–NIR of the CdS thin films are also provided in Figure S5 and S6, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The result was because CdCl 2 can serve as the assisted melting reagent. [ 14 ] Therefore, the compact and full‐coverage CdS thin films with thickness of 50 ± 6 nm can be obtained using the low concentration of ammonia (0.59 m ).…”
Section: Resultsmentioning
confidence: 99%
“…[31] The loading force is generated by the 2000 kN Paris-Edinburgh press. [32] An iron cylinder (99.99%, Alfa Aesar, US) with a size of Φ2 × 2 mm was used as a sample. The sample pressure was continuously monitored in situ by using the equation of state (EOS) of crystalline Fe.…”
Section: Pressure Calibration Experimentsmentioning
confidence: 99%